The influence of the library and the school literacy movement on students' learning interest in the Gangsa primary school - Sopianda; Riady, Yasir (Mitra Palupi, 2024)
Background: The library is a supporting tool in increasing students' interest in learning. Purpose: This study describes the influence of the library and the implementation of the school literacy movement at SDN Gangsa on students' interest in learning, which consists of habituation, development and learning and the obstacles at Gangsa State Elementary School. Design and methods: The research method applied in this research is a quantitative research method. The research was carried out by observing data on the number of library visitors at the school. Results: The research results show that the implementation of the school literacy movement has been running. However, there are still obstacles to its implementation, such as problems with the time for implementing literacy activities, lack of reading collections, lack of teacher commitment in carrying out habitual reading activities in the library and the classroom, and changes in policy from the school principal. The importance of literacy habits for students. The presence of a library and literacy movement at Gangsa State Elementary School greatly influences students' interest in learning. This can be seen from the increasing interest of students in visiting the library to read. Data on library visitors after the literacy movement was implemented at the Gangsa State Elementary School, increased by 60% from before the literacy movement was implemented at the school, and it is hoped that the presence of the library and the literacy movement implemented can increase students' interest in learning on an ongoing basis.